TESTE DE BOMBEAMENTO OBJETIVANDO O APROVEITAMENTO DE ÁGUAS MINERAIS EM MEIO POROSO - Lima, Alípio Agra; Vieira Filho, José Augusto; Anjos, Florísio Tabosa dos; Tavares, Marcos Antônio de Holanda (Águas Subterrâneas, 2001)
Resumo não disponível.